2010
DOI: 10.1016/j.otohns.2010.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related hearing loss, vitamin B12, and folate in the elderly

Abstract: Serum folate was significantly lower among elderly with ARHL. Trials on nutritional supplementation may substantiate the role of serum folate in ARHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 23 publications
3
32
0
4
Order By: Relevance
“…Reduced folic acid (FA) concentrations have been found in age-related HL (ARHL) and sudden SNHL, this decrease correlating with either reduced vitamin B 12 (Houston et al, 1999; Lasisi et al, 2010; Karli et al, 2013) or increased tHcy levels (Cadoni et al, 2004). Although Hcy concentrations reflect alterations in its metabolism (Figure 1), which include the methionine and folate cycles, as well as the transsulfuration pathway, no consistent association between mutations in genes of these pathways and SNHL has been reported (Durga et al, 2006; Uchida et al, 2011).…”
Section: Hyperhomocysteinemia and Neurosensorial Hearing Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced folic acid (FA) concentrations have been found in age-related HL (ARHL) and sudden SNHL, this decrease correlating with either reduced vitamin B 12 (Houston et al, 1999; Lasisi et al, 2010; Karli et al, 2013) or increased tHcy levels (Cadoni et al, 2004). Although Hcy concentrations reflect alterations in its metabolism (Figure 1), which include the methionine and folate cycles, as well as the transsulfuration pathway, no consistent association between mutations in genes of these pathways and SNHL has been reported (Durga et al, 2006; Uchida et al, 2011).…”
Section: Hyperhomocysteinemia and Neurosensorial Hearing Lossmentioning
confidence: 99%
“…To date, supplementation and nutrient deficiency studies have been conducted using laboratory animals, in which auditory thresholds, internal ear microvasculature, or inflammation have been evaluated (Schuknecht et al, 1974; Makishima, 1978); but only a few have analyzed Hcy metabolism following the lead of the epidemiological data (Houston et al, 1999; Cadoni et al, 2004; Lasisi et al, 2010). Two studies in mouse models have shown the relationship between Hcy metabolism and SNHL and the impact of folate deficiency (FD; Martínez-Vega et al, 2015a, 2016).…”
Section: Nutritional Interventions and Hearing Lossmentioning
confidence: 99%
“…The relationship between nutritional deficiencies in vitamins, including folate deficiency, and hearing loss has been explored in a variety of epidemiological studies (Houston et al, 1999; Cadoni et al, 2004; Lasisi et al, 2010; Attias et al, 2012; Karli et al, 2013). However, the data obtained have not always been consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as noise and ototoxic drugs are well-known effectors of this impairment, but more recently several epidemiological studies have shown the association between the nutritional status and hearing loss. Precisely, inadequate levels of folic acid have been correlated with hearing loss in the presence of reduced vitamin B 12 concentrations or hyperhomocysteinemia (Houston et al, 1999; Cadoni et al, 2004; Lasisi et al, 2010). Additional reports have explored the putative association of mutations in genes of the folate cycle and the impact of hearing loss, their results being somewhat inconsistent (Durga et al, 2006; Uchida et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, targeting mitochondria is becoming increasingly popular [82], and there were some successful attempts in treatment of hearing conditions using mitochondrial supplements [83][84][85][86][87][88][89].…”
Section: Mitochondrial Toxicity: Common Denominator Of Ototoxic Drugsmentioning
confidence: 99%